Extension control strategy of a single converter for hybrid PEMFC/battery power source. (5th January 2018) - Lü, Xueqin; Miao, Xing; Liu, Wenming; Lü, Jian
Highlights: Investigation of the dynamic behavior of the PEMFC/battery hybrid power system. Energy management method of the PEMFC/ battery hybrid power system based on extension control technique. Using the state distance Ds to replace the original parameters to improve the robustness of the control system. Abstract: This paper describes a control scheme to improve the dynamic characteristics of a PEMFC/battery hybrid power system. The proposed control scheme includes a power control strategy to control the power flow of the PEMFC/battery hybrid system and an extension control for the DC/DC converter of the PEMFC. The power control strategy enables the fuel cell to operate within the high efficiency region. The DC/DC converter with the extension control is applied to control the fuel cell output power. In order to solve the problem that the parameter tuning of the extension control depends on human experience and is difficult to be determined, the extension control method is improved, which uses the state distance Ds to replace the original parameters to solve the difficult problem of parameter tuning. Finally, the experimental results on a 500 W fuel cell/24 V, 10 A h Li-ion battery hybrid system are given to verify the good tracking response, low ripple of output current and short response time of the hybrid system outputs.